2010
DOI: 10.1080/17470919.2010.503618
|View full text |Cite
|
Sign up to set email alerts
|

Infantile experience and play motivation

Abstract: Fully-fledged affective systems in mature animals are in part the result of the impact of infantile experience on brain development. The present experimental series examines whether tactile stimulation in infancy (early handling) influences rough-and-tumble play (R&T) throughout the juvenile period, using a testing regime of 17 days divided into five parts where handled (H) and nonhandled (NH) Wistar rats are assessed daily. In Parts 1 and 2 (age range at the start: 30-33 days) the objective is to study the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
2
3
0
Order By: Relevance
“…When subjects were tested with their cage mate, we found no sex differences in any strain, similar to what Himmler et al (2014Himmler et al ( , 2013 reported, and what others have found, particularly in Long-Evans and Wistar rats (Aguilar, 2010;Bredewold et al, 2015Bredewold et al, , 2014Holloway & Suter, 2004;Loranca & Salas, 2001;Northcutt & Nguyen, 2014;Panksepp, 1981;Paul et al, 2014;Siviy & Panksepp, 1985, 1987Smith & Northcutt, 2018;Thor & Holloway, 1984;Veenema et al, 2013;Zimmerberg & Sageser, 2011). In contrast, when tested with an unfamiliar sibling, the only sex difference we found was in the opposite direction: female Long-Evans rats played more than males.…”
Section: Sex Differences In Playsupporting
confidence: 90%
See 1 more Smart Citation
“…When subjects were tested with their cage mate, we found no sex differences in any strain, similar to what Himmler et al (2014Himmler et al ( , 2013 reported, and what others have found, particularly in Long-Evans and Wistar rats (Aguilar, 2010;Bredewold et al, 2015Bredewold et al, , 2014Holloway & Suter, 2004;Loranca & Salas, 2001;Northcutt & Nguyen, 2014;Panksepp, 1981;Paul et al, 2014;Siviy & Panksepp, 1985, 1987Smith & Northcutt, 2018;Thor & Holloway, 1984;Veenema et al, 2013;Zimmerberg & Sageser, 2011). In contrast, when tested with an unfamiliar sibling, the only sex difference we found was in the opposite direction: female Long-Evans rats played more than males.…”
Section: Sex Differences In Playsupporting
confidence: 90%
“…However, four studies have reported some female-biased sex differences in this strain (Field, Whishaw, Pellis, & Watson, 2006;Madden & Zup, 2014;Mychasiuk, Hehar, Farran, & Esser, 2014;Wood, Molina, Wagner, & Spear, 1995). Finally, approximately two-thirds of studies in Wistar rats find no sex differences in behavior (Aguilar, 2010;Bredewold, Schiavo, van der Hart, Verreij, & Veenema, 2015;Bredewold, Smith, Dumais, & Veenema, 2014;Himmler et al, 2014;Holloway & Suter, 2004;Loranca & Salas, 2001;Paul et al, 2014;Veenema, Bredewold, & De Vries, 2013); those that do tend to report more modest sex differences (Taylor et al, 2012). Although these analyses can provide some insight into potential strain differences, these three strains have never been directly compared to one another in a single experiment.…”
mentioning
confidence: 99%
“…This suggests that being paired with a handled rat changed the behavior of the target rat and likely reflects the contagious nature of play (Pellis & McKenna, 1992; Reinhart et al, 2006). These data, combined with the subtle effects of handling described above for LEW rats and the increased likelihood of rotating completely to a supine position, support previous research (Aguilar, 2010; Aguilar et al, 2009; Siviy & Harrison, 2008) showing that neonatal handling can increase playfulness in rats. With these data in mind we can also tentatively conclude that neonatal handling may be enhancing the motivation to play in LEW rats and that this is most likely to be detected when baseline levels of play are at a sub-maximal level (e.g., after 4 hours of social isolation).…”
Section: Discussionsupporting
confidence: 85%
“…Short separations from the mother tend to produce offspring that display improved capacities to manage a social or physical challenge (Levine, 2005; Aguilar, 2010; Zanettini et al, 2010), though this was not true in every study (Todeschin et al, 2009); while either drastically reduced handling or long separations tend to produce offspring that are hyper-responsive to stressors (Levine, 2002a). It is often hypothesized that this effect is maternally mediated, possibly due to increases in maternal attention to infants upon reunion, although alternative hypotheses have also been suggested (Denenberg et al, 1962; Denenberg and Whimbey, 1963; Smotherman and Bell, 1980; Boccia and Pedersen, 2001; Tang, 2001; Tang et al, 2006; Macri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%